INCIDENCIA DE LOS ACTIVADORES DE JUICIOS DE METAMEMORIA Y SUGERENCIAS DE ESTRATEGIAS EN EL APRENDIZAJE AUTÓNOMO - Maldonado Granados, Luis Facundo (Tecné, Episteme y Didaxis: TED, 2000)
Develop skills for autonomous learning is a challenge for educational systems in the current knowledge society. ln fact, as information and knowledge production increases update learning becomes a necessary condition for person and enterprise achievement. Three questions are at the core of this paper: a- if metamemory judgment activators increase problem solution; b- lf suggestion of strategy facilitates learning of problem solving; and c- if strong strategy learning generalizes for handling new problems. An experimental study was conducted using discovery problems on spatial reasoning. 9 computer games were programmed to support 4 experimental conditions: a) With metammemory judgment activators and strategy suggestion, b) With meta-memory judgment activa tors and no strategy suggestion, c) Without meta-memory judgment activators and with strategy suggestion, and d- With no meta-memory judgment activators and no strategy suggestion. 150 high school students were randomly assigned to the experimental conditions. Statistical analysis uses factor analysis of variance and regression analysis. A simulation program allows reproducing the sequence of transition states followed by the problem solvers and identifying solution strategies. Metamemory judgements activators effects are interpreted in the frame of a motivational micro-system. Strategy suggestion operates after some basic experience on the task environment and mainly after the first success of solving the problem. Strategy generalization is evident among the initial stages of the learning curve of different problems.